Faktor-Faktor Penghambat Guru dalam Pembelajaran Geografi pada Masa Pandemi Covid-19 di SMA Negeri 1 Toli-Toli - Eko B, Fransiskus; Amiruddin (Jurpis: Jurnal Pendidikan Ilmu Sosial, 2023)
This study aims to find out what are the inhibiting factors and what are the teacher's efforts in overcoming obstacles in learning geography during the COVID-19 pandemic at SMA Negeri 1 Toli-Toli. The method used is descriptive qualitative, with research subjects 2 teachers of geography. Data collection techniques by observation, interviews and documentation. The research instrument used interview guidelines. The data analysis used is interactive model data analysis. The results of the study show that the first; inhibiting factors in learning geography during the COVID-19 pandemic at SMA Negeri 1 Toli-Toli, which really dominated were internet nets, data pulses, and smartphone ownership for students. In addition, communication factors, lack of interest in student learning, online learning methods, and slow delivery of material occur to students. Second; the efforts of schools and teachers to overcome barriers to online learning, namely: 1) Students to take part in online learning at schools for students who are constrained by networks and smartphones; 2) the teacher communicates personally through communication with WhatsApp; 3) the teacher motivates the students; 4) lecture and assignment methods are quite simple and make it easier for students; 5) some students do not like learning geography after the teacher has identified it; 6) the factors of facilities and infrastructure for learning geography are very supportive and quite good.